Ukay-ukay business operation in Bulihan Silang, Cavite : an assessment - Castillo, Arianne Joy M. (Manila: National University, 2005)
This study aims to investigate on the situation of the ukay-ukay industry in the Philippines.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of Table -- Chapter 1. The Problem and its background -- Chapter 2. Review of related literature -- Chapter 3. Research Methodology -- Chapter 4. Presentation, analysis, and interpretation -- Chapter 5. Summary of Findings, Conclusion, and Recommendation -- Appendix -- Bibliography.
Research Method : Descriptive Research Design
Includes bibliography.